DISTANCE EDUCATION AS AN ALTERNATIVE FORM OF LEARNING IN A PANDEMIC CONDITION - Kuchynska, Iryna; Bobkovych, Kateryna; Davydova, Nataliia; Polishchuk, Svitlana; Shumeiko, Olha; Prysiazniuk, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The aim of the research is to analyze the relationship between the success and frequency of the distance learning server Moodle using in the study of medical students, as well as to assess the features and identify major problems in training during COVID-19 pandemic. The results of 200 medical students total success have been analyzed. Students’ education achievement was assessed as a factor in determining the training success in the context of relationship with the number of Moodle distance learning server visits. Two subgroups have been analyzed (100 people in each) depending on the departments: сlinical discipline (propaedeutics of іnternal medicine) and theoretical (biochemistry). Statistical analysis of students’ activity in Moodle system revealed high correlation between the frequency of the platform visits and students’ educational success at the Department of Propaedeutics of Internal Medicine. A similar pattern is observed in the analysis of the correlation between the use of Moodle and learning outcomes in theoretical disciplines by the example of Bioorganic and biological chemistry and clinical biochemistry department. Thus, in order to prevent the spread of acute respiratory disease COVID-19, an distance education elements should be implemented; the using of the Moodle platform helps to increase medical student’s educational success.